SCOR-Based Information Modeling for Managing Supply Chain Performance of Palm Oil Industry at Riau and Jambi Provinces, Indonesia - Djatna, Taufik; Marimin, Marimin; Massijaya, Muh. Yusram; Asrol, Muhammad; Baidowi, Taufiq; Harison, Harison; Safriyana, Safriyana; Martini, Sri (International Journal of Supply Chain Management, 2020)
Abstract— The challenges for providing a concise performance reports along all components in Palm Oil agro-industry supply chain are urgent particularly in terms of managing each metrics of the stakeholders. This SCOR (Supply Chain Operation Reference)-based information model attempts to represent real requirements of each stakeholder. Initially, all relevance stakeholders are identified through field observation and interviews. Each SCOR model attribute, i.e. agility, assets, cost, reliability and responsiveness are mapped into respectfully definition in the field of Palm Oil agro-industry. The related attribute is derived into metrics of evaluation for measuring specific performance according to the formulation. In order to report a definitive performance measurement in each attribute, benchmarking from best practice is taken. This model functionality is evaluated by using real world data derived from two major provinces of Palm Oil agro-industry in Indonesia, namely Jambi and Riau provinces. Object relational database is generated and stationed in a cloud-based server. A framework of business process modeling and notation integrates these required processes of the model with the cloud-based database access. The integration of JavaScript (Bonita soft) based front-end with the SCOR-based database operation is ready for mobile and desktop usage. A series of visualization is provided to support fast understanding in each performance measurement, such us spider chart, histogram and line chart as well as ETL (extract, transform, load) features. A full comparison based on geographical location is ready for inquiry for each user level (farmer, trader and palm oil mill).Keywords—Agro-industry, Information, Palm Oil, Performance, SCOR